Modern Laser Scanning Confocal Microscopy. Issue 1 (20th June 2018) - Bayguinov, Peter O.; Oakley, Dennis M.; Shih, Chien‐Cheng; Geanon, Daniel J.; Joens, Matthew S.; Fitzpatrick, James A. J.
Abstract: Since its commercialization in the late 1980's, confocal laser scanning microscopy (CLSM) has since become one of the most prevalent fluorescence microscopy techniques for three‐dimensional structural studies of biological cells and tissues. The flexibility of the approach has enabled its application in a diverse array of studies, from the fast imaging of dynamic processes in living cells, to meticulous morphological analyses of tissues, and co‐localization of protein expression patterns. In this chapter, we introduce the principles of confocal microscopy and discuss how the approach has become a mainstay in the biological sciences. We describe the components of a CLSM system and assess how modern implementations of the approach have further expanded the use of the technique. Finally, we briefly outline some practical considerations to take into account when acquiring data using a CLSM system. © 2018 by John Wiley & Sons, Inc.